ChemInform Abstract: New Tetramethylthiepinium (TMTI) for Copper‐Free Click Chemistry. Issue 2 (9th January 2013) - King, Mathias; Baati, Rachid; Wagner, Alain
Abstract The title compound (I) is stable towards amines, alcohols and carboxylic acids.